Imunolocalização da metalotioneína no adenoma pleomórfico de glândula salivar: correlações clínico-patológicas - Alessandra de Castro Miranda (2012)
Pleomorphic adenoma (PA) is the most common benign neoplasm of major and minor salivary glands. The tumor growth is slow; however, PA can reach large dimensions, mainly when located in the parotid gland. The histological features are very diversified with the involvement of epithelial-myoepithelial structures. Metallothionein (MT) is a cysteine rich protein present in myoepithelial cells of several benign and malignant neoplasms. MT has its function associated with DNA protection, oxidative stress and apoptosis. The purpose of this study was to evaluate the expression of MT in PAs. Additionally, we investigated the association of the clinicopathologic features of the lesions with MT, and specifically, the correlation of Bcl-2 with MT in an attempt of evaluate the role of MT in the control of apoptosis in the PAs. Thirty five cases of PA of minor salivary gland were selected and immunohistochemistry was performed for Bcl-2 and MT proteins. The expression of these proteins was analyzed by the "QuickScore" method. The sample showed epidemiological characteristics similar of those described in the literature. We did not find association between the clinicopathologic characteristics of PAs and the immunoexpression of the proteins studied, but a correlation between Bcl-2 and MT was demonstred. The results suggest that MT may have a role in the control of apoptosis in PA.